2012
DOI: 10.1007/s12083-012-0137-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection and mitigation of localized attacks in a widely deployed P2P network

Abstract: Several large scale P2P networks operating on the Internet are based on a Distributed Hash Table. These networks offer valuable services, but they all suffer from a critical issue allowing malicious nodes to be inserted in specific places on the DHT for undesirable purposes (monitoring, distributed denial of service, pollution, etc.). While several attacks and attack scenarios have been documented, few studies have measured the actual deployment of such attacks and none of the documented countermeasures have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The influence of adversarial nodes in P2P networks has been thoroughly researched in [10][11][12], with recent work focusing on DLT networks such as Ethereum [13][14][15][16][17] and Bitcoin [7,17,18]. The identified problems are diverse and include, but are not limited to the following: Eclipse Attacks, DoS and DDoS attacks, manipulation of routing advertisements (i.e., BGP hijacks), man-in-the-middle attacks and Sybil attacks (a recent study reported a Sybil attack that was executed on the Bitcoin Cash network with up to 5000 Sybil nodes [19]).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of adversarial nodes in P2P networks has been thoroughly researched in [10][11][12], with recent work focusing on DLT networks such as Ethereum [13][14][15][16][17] and Bitcoin [7,17,18]. The identified problems are diverse and include, but are not limited to the following: Eclipse Attacks, DoS and DDoS attacks, manipulation of routing advertisements (i.e., BGP hijacks), man-in-the-middle attacks and Sybil attacks (a recent study reported a Sybil attack that was executed on the Bitcoin Cash network with up to 5000 Sybil nodes [19]).…”
Section: Related Workmentioning
confidence: 99%
“…In a loop, APREQ and APRES messages are exchanged and the contents of the APRES messages are used to update α (lines (6-8)). A random, uncontacted node from S h is used for the next hop (lines (11)(12)). If d hops were made (line (5)), or z reaches (0) (line (9)), the walk ends and the result is returned (line ( 14)).…”
Section: Aurora Algorithmmentioning
confidence: 99%
“…In the wider literature, various methods to limit this type of attack have been proposed. These methods can be classified based on the following parameters:  Strong identification of peers [35]  Authentication and authorization [36]  Trust score [37] ■ Eclipse attack. In a network, many versions of this attack are possible.…”
Section: Attacksmentioning
confidence: 99%
“…Several researchers [6], [7] have reported ongoing Sybil attacks in the KAD network, and even performed it themselves for research purposes. Therefore multiple works in the literature [8] have proposed solutions to prevent or mitigate the harm produced by Sybil attacks.…”
Section: Using a Sybil Attack Against Dht Resourcesmentioning
confidence: 99%
“…Some of the most popular DHT systems like KAD, the one employed by the eMule file-sharing network, or the two main DHTs associated to BitTorrent, account for millions of concurrently connected users. In particular, Steiner et al [12], and more recently Cholez et al [7], reported that the number of users concurrently connected to the KAD network varies between 3.3 and 4.5 millions. Furthermore, the minimum number of replicas of KAD resources is r = 10.…”
Section: Vulnerability Of Dht Systems To Sybil Resource Attacksmentioning
confidence: 99%